Embedded System Using Field Programmable Gate Array (FPGA) myRIO and LabVIEW Programming to Obtain Data Patern Emission of Car Engine Combustion Categories - - Andrizal; Rivanol Chadry; Ade Irma Suryani (JOIV : International Journal on Informatics Visualization, 2018)
Engine scanner unit is a tool used by mechanical power to know the condition of car engine combustion at the time of tune up process done. The level of elements and compounds that dominant in determining categories of combustion of gasoline fuel car engines through the levels of elements and compounds contained in exhaust emissions are Hydrocarbons (HC), Carbon Monoxide (CO), Carbon Dioxide (CO2) and Oxygen (O2). Complete combustion category produces maximum power, fuel efficiency and emission levels according to the threshold. This occurs when there is a balance of the amount of fuel, airflow and ignition in the engine combustion chamber. Elements and compounds contained in car exhaust emissions can be detected with sensors that are sensitive to elemental levels and these compounds are HC, CO, CO2, and O2 sensors. This study aims to display the data pattern category of combustion engine through exhaust emissions based on multi sensor detection processed with signal processing system in the form of Fast Fourier Transform (FFT) process. Furthermore, data pattern is performed in accordance with the category of combustion engine detected. The system is designed with embedded system using Field Programable Gate Array (FPGA) myRIO and LabVIEW programming. The results in the test displays the data pattern and the comparison test of the reference data pattern with the data pattern of the detection result. The comparison test result of data pattern similar to 87% complete engine combustion category and similar to incomplete combustion category 90%.